Spectroscopic Studies and Thermal Analysis of New Azo Dyes Ligands and their Complexes with some Transition of Metal Ions (Baghdad Science Journal, 2018)
New Azo ligands HL1 [2-Hydroxy-3-((5-mercapto-1,3,4-thiadiazol-2-yl)diazenyl)-1-naphth aldehyde] and HL2 [3-((1,5-Dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)diazenyl)-2-hydroxy-1-naphthaldehyde] have been synthesized from reaction (2-hydroxy-1-naphthaldehyde) and (5-amino-1,3,4-thiadiazole-2-thiol) for HL1 and (4-amino-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one) for HL2. Then, its metal ions complexes are synthesized with the general formula; [CrHL1Cl3(H2O)], [VOHL1(SO4)] [ML1Cl(H2O)] where M = Mn(II), Co(II), Ni(II) and Cu(II), and general formula; [Cr(L2)2 ]Cl and [M(L2)2] where M = VO(II), Mn(II), Co(II), Ni(II) and Cu(II) are reported. The ligands and their metal complexes are characterized by phisco- chemical spectroscopic techniques (FT.IR, Mass, UV-Vis, 1H and 13C-NMR, TGA, (C.H.N.), molar conductivity, Atomic Absorbance, Chloride containing magnetic susceptibility). The spectral data suggest that the (HL1) behaves as a bidentate ligand in all complexes, whereas (HL2) behaves as a tridentate ligand for all complexes; bidentate ligand in Vanadium complex is coordinated with the metal ions through azo nitrogen and oxygen atoms. Theoretical studies of these ligands and their metal complexes in gas phase using Hyper chem.8. Studies of these compounds are prepared for their bacterial activity